Experimental data acquisition and mathematical model for soluble protein extraction from Argentinian extruded expeller soybean meal - Accoroni, Cecilia; Godoy, Ezequiel; Reinheimer, María Agustina (Springer, 2025)
Extruded expeller soybean meal is a byproduct of the soybean oil extraction, which is frequently used in Argentina by animal feed millers. In this work, the soluble protein extraction stage is studied as the first step of a challenge project in order to obtain a soy protein product from this byproduct. Extruded expeller meals from 4 different Argentinian processing plants were used to obtain 41 experimental data sets, using 1 to 3 consecutive extraction cycles operating at temperatures from 55 to 65 °C. Firstly, 16 data sets were used to estimate the values of the distribution constant and the diffusivity of proteins within the particle, both as function of the extraction temperature. The remaining 25 data sets were used for validation purposes. Extraction yields were analyzed considering the impact of the operating conditions, while a good agreement between experimental and predicted extraction yields was achieved as the reported statistical parameters indicate.